Masculinity, Mental Health, and Desire for Social Support Among Male Cancer and Infertility Patients. Issue 1 (February 2019) - Miner, Skye A.; Daumler, Davis; Chan, Peter; Gupta, Abha; Lo, Kirk; Zelkowitz, Phyllis
By surveying men who are currently infertile ( N = 251) and men who are potentially infertile (i.e., men with cancer; N = 195), the mental health consequences of reproductive masculinity, or the cultural assumption that men are virile and should be fathers, were investigated. There was no difference in depression levels between these two groups when controlling for demographic variables, suggesting that both groups of men have similar mental health needs. Since gendered notions of masculinity also suggest that men do not want to discuss their fertility health, their desire for online fertility-related social support was assessed. These findings suggest that most men do want to talk to others about fertility, which indicates that there is a need for more fertility-related social support. This research challenges some conceptions regarding masculinity, as men revealed an interest in accessing online social support related to fertility.